Evolution of means of consumption and urban transformation - Pecile, Paolo (Scienze del Territorio, 2022)
The studies that highlight the central role of consumption in the so called ‘postmodern’ society make evident the effect that the prevalence of new means of consumption have on the image of cities and their very structure. The spectacularization of merchandise and the transformation of purchasing into new forms of experience produce a kind of screaming architecture that trivializes the perception of the architectural space and has a profound impact on the city, its appearance, its functions, its mode of exploitation and its own meaning. Finally, a situation is envisaged concerning the effects of the recent acceleration of e-commerce which could lead to the aggravation of the solitary habits of the consumer, depriving him of what remains of sociability in current retail spaces.